2023
DOI: 10.3390/children10040742
|View full text |Cite
|
Sign up to set email alerts
|

The Relations between Repetitive Behaviors and Family Accommodation among Children with Autism: A Mixed-Methods Study

Abstract: Restricted and repetitive behaviors and interests (RRBI) are a significant component in diagnosing autism spectrum disorder (ASD). They often pose the main challenge in day-to-day functions for children with ASD and their families. Research addressing family accommodation behaviors (FAB) in the ASD population is scarce, and associations with the characteristics of the children’s behaviors are unclear. This sequential mixed-methods study assessed the correlation between RRBI and FAB within the ASD group to deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Therefore, considering that parenting style can affect the autistic child’s stress levels, there may be a correlation between parenting style and the severity of RRBs. Furthermore, RRBs not only impact the autistic individual but also require family accommodation behaviors (FAB) [ 25 ]. FABs encompass the actions taken by the family to help the autistic child adjust to their environment by implementing routines that assist the child in coping with different situations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considering that parenting style can affect the autistic child’s stress levels, there may be a correlation between parenting style and the severity of RRBs. Furthermore, RRBs not only impact the autistic individual but also require family accommodation behaviors (FAB) [ 25 ]. FABs encompass the actions taken by the family to help the autistic child adjust to their environment by implementing routines that assist the child in coping with different situations.…”
Section: Discussionmentioning
confidence: 99%
“… 30 In recent years, researchers have discovered significant positive correlations between restricted and repetitive behaviors and interests and overall family accommodation behaviors and their sub scores in children with autism spectrum disorder. 31 Research has also shown that family accommodation and child anxiety are bidirectionally related between the age 4 years and school age, 32 and youths with anxiety disorders report greater family accommodation than control groups. 33 In addition, family accommodation of restricted and repetitive behaviors occurs frequently and is linked to greater symptom severity in families of children with autism 34 and family accommodation can have a significant impact on the child’s anxiety.…”
Section: Introductionmentioning
confidence: 99%